A Rasch Analysis on Tourism Business in Covid-19 Era: The Attactiveness of Taman Mini Indonesia Indah (TMII) Jakarta - Erma Lusia; Maria Grace Herlina (Journal of Business and Behavioural Entrepreneurship, 2021)
The SARS-CoV-2 pandemic impacts health, the economy, and the environment (also known as COVID19). It's no secret that tourism has been hit particularly hard during the Covid-19 era. Nevertheless, many people continue to search for a tourist destination despite the covid-19 health protocol. Individuals tend to stay home during an outbreak, and large families with young children travel shorter distances than other tourist groups. Local visitors continue to be interested in TMII as a domestic tourism destination as 74 percent of visitors want to visit TMII. Analysis of TMII's amenities and ancillary services using the Rasch Model revealed the most attractive destination attributes. However, when it comes to transportation options, they are by far the least appealing.